DEVELOPMENT OF A SCIENCE (CHEMISTRY) PROJECT TEACHING MODULE IN THE MERDEKA CURRICULUM AS A TEACHER’S GUIDE FOR LEARNING IN CLASS X VOCATIONAL SCHOOLS - Diva, Felia Aura; Muntari; Junaidi, Eka (UIN Mataram, 2024)
This research is a development research that aims to produce an IPAS (Chemistry) Project teaching module as a teacher's guide in learning, which is feasible in terms of validity and practicality. This module development adapts the 4D model (Define, Design, Develop, Disseminate) because the stages are arranged in detail and systematically, involving revisions, trials, and validation by experts. The test subjects were class X students of SMKN 1 Narmada with the Agribusiness of Agricultural Product Processing (APHP) expertise program. The research instruments included validation sheets and student and teacher response questionnaires. Data analysis used descriptive statistics, with module validity calculated using Aiken's V formula, and module practicality analyzed using a Likert scale. The results showed the average validity of the four validators was 0.861, which was classified as very valid. The level of understanding between validators was tested using the Percentage of Agreement (R) method, resulting in an average of 0.90 with a reliable category. The practicality of the module based on teacher and learner response questionnaires showed an average percentage of 94% and 81%, respectively. Based on these results, it can be concluded that the IPAS (Chemistry) Project teaching module on substance material and its changes for class X SMK has a high level of validity and practicality, so it is suitable for use in the learning process.